Shear Behavior of RC Beams Strengthened by External Vertical Prestressing Rebar - Ying Li; Meizhong Wu; Weiqi Wang; Xingwei Xue (Advances in Civil Engineering)
Shear design is an important part of structural design. External vertical prestressing rebars (EVPRs) have proven to be an effective way to enhance structural shear resistance. The objectives of this study are to simulate EVPR strengthening of concrete beams using a nonlinear three-dimensional finite element model and to explore its shear enhancement features under different EVPR stirrup ratios, vertical compressive stress degrees, and optimal arrangements of EVPRs. Concrete, common reinforced bars, and EVPRs use solid, steel, and truss elements, respectively. In addition, the total strain crack model is used to characterise the concrete. The results indicate that the EVPR stirrup ratio can reduce the diagonal crack width and improve the shear capacity, and the vertical compressive stress degree can effectively control crack development in the initial loading. A “small-area EVPR dense arrangement” is the recommended EVPR configuration method. Both experiments and numerical analyses show that EVPRs can effectively improve the shear performance of concrete.